Evaluation of the hemogram in healthy canines under cisplatin therapy - Calpa O, Carlos; Daleck, Carlos [UNESP]; de Castro, Joao Teotonio [UNESP] (Univ Cordoba, 2010)
Objective. To evaluate the average values of the hemogram test in healthy dogs during chemotherapy with cisplatin. Materials and methods. The hemogram parameters of eight healthy canines, which underwent therapy with cisplatin, were evaluated. These canines were divided into two groups. The dogs in the first group were given cisplatin (70mg/m(2), i.v.) and to prevent kidney poisoning they were given physiological serum at 0.9% (25mL/kg/h, i.v.). The dogs in group two were not given cisplatin. Results. The hemogram of the dogs in the first group did not show any significant difference (p>0.05) as compared to the dogs in group 2.Conclusions. The data obtained indicate the protocol used with cisplatine does not significantly alter the average values of the hemogram test and the number of chemotherapy sessions increases the risk of diminishing the values of the hemogram test.

Objetivo. Evaluar los valores medios del hemograma en perros sanos durante la quimioterapia con cisplatina. Materiales y métodos. Se evaluaron los parámetros del hemograma de ocho caninos sanos sometidos a terapia con cisplatina, distribuidos en dos grupos. A los perros del grupo uno se les administró cisplatina (70 mg/m2, i.v.) y para prevenir la nefrotoxicidad recibieron suero fisiológico al 0.9% (25mL/kg/h, i.v.). Los animales del grupo dos no recibieron cisplatina. Resultados. El hemograma de los perros del grupo uno no mostró diferencia significativa (p>0.05) con respecto al de los animales del grupo dos. Conclusiones. Los datos obtenidos indicaron que el protocolo con cisplastina no alteró significativamente los valores medios del hemograma y el número de sesiones de quimioterapia aumenta el riesgo de disminución de los valores del hemograma.
Evaluación del hemograma en caninos sanos sometidos a la administracion de cisplatina
Keywords: Cisplatin; Chemotherapy; hemogram test; haemoglobin; white blood cells; Dog